Education of the Girl Child Present Status and Steps for Promotion - Singh, Ajit (THE PRIMARY TEACHER, 2009)
Education is a basic human right. It is essential for developing human resources. It is a means of fighting poverty at all stages and in different contexts. Professor Amartya Sen, the Nobel laureate says "the economies that have been most successful in the recent development of world trade, namely Japan, Taiwan, Singapore and now China, have all been very oriented towards basic education. Unfortunately in India, education is still a neglected and underappreciated value." Therefore, at all the levels of education, primary education or basic education is a must. This is because it develops among individuals necessary knowledge and skills to earn their livelihood and meet their basic needs. It is an indispensable passport to life. Since independence in 1947, India has been making incessant efforts to achieve Education For All (EFA). Endeavours to attain EFA gained impetus after the international community gathered for first time in Jomtein in 1990 and adopted a resolution to achieve Education For All by 2000. The World Education Forum, Dakar Senegal which met in April 2000 committed that the international community must ensure universal access to quality basic education. It is to be achieved and sustained by 2015. India is a party to the Dakar Convention. India has launched programmes such as District Primary Education Project (DPEP) and Sarva Shiksha Abhiyan (SSA) to achieve the goal. Enormous human and material resources are being invested to achieve education for all. All these endeavours have not taken us to achieve our EFA goal. Table 1 manifests the net enrolment ratio at the primary level.